Managing Diversity and Inclusion : An International Perspective - Syed, Jawad (SAGE Publications, Ltd. (UK), 2019)
Written and edited by leading experts in the field, this authoritative account sets UK and European practices firmly within a global context. It offers an in-depth and contextual account of enduring, contemporary and cutting edge theories and approaches to diversity and inclusion management. With workforce demographics changing rapidly, high-profile cases of discrimination in the news and new legislation coming into force, it is more crucial than ever that organisations understand and effectively manage workplace diversity – not only to increase business outcomes, but to create an inclusive workplace in a socially responsible manner. This second edition includes an engaging new chapter on social class and diversity, as well as a range of new mini case studies on contemporary issues and themes such as intersectionality and autism employment. Packed with learning features to encourage critical analysis and help you link theory to real-world practice, Managing Diversity and Inclusion offers an in-depth and contextual account of enduring and cutting edge discussions and approaches to diversity and inclusion management.